From Cronyism to Oligarchy? Privatisation and Business Elites in Myanmar - Ford, M.; Gillan, M.; Thein, Htwe Htwe (Routledge Taylor & Francis Group, 2015)
Privatisation is often contentious yet in Myanmar it has not so much been its merits or drawbacks that have attracted attention as questions around implementation. In Myanmar, the implementation of privatisation has broad significance for the political economy. A first phase of privatisation was focused on small and medium-sized enterprises and did not have a significant economic impact. A second phase, commenced in 2008, consolidated the interests of a business elite with personal connections to the military regime. The impact of this second phase of privatisation was such that some elements of this elite strengthened to the extent that they no longer relied entirely on patronage, creating opportunities for diversification in their strategies of wealth creation and defence. For this reason, it is argued, the wealthiest strata of Myanmar’s business elite is now best conceived as not simply consisting of cronies but rather as a nascent form of oligarchy. In theoretical terms, this suggests that greater attention to the qualitative difference between cronyism and oligarchy is warranted, as is close study of processes – like privatisation and political reform – that enable or require a wider range of strategies of wealth defence.